The Influence of Digital-Based Flashcard Media Using Global Methods for the Beginning Reading Ability of Class I Students at SD Negeri 116 Pekanbaru - Sri Nurhidayati; Febrina Dafit (Journal of Education Technology Information Social Sciences and Health, 2024)
This research is based on the low initial reading ability of IB class students of SD Negeri 116 Pekanbaru. This study aims to find out how much influence digital-based flashcard media with global methods has on the initial reading ability of students in grade I of SD Negeri 116 Pekanbaru. This type of research is a quantitative research with the quasy experimental method. The data collection technique is by conducting a reading test to students. The population in this study is class I students consisting of three classes with a total of 94 students, IB class consists of 32 students as an experimental class and class IA consists of 31 students as a control class. The results of this study show that the reading ability of students in the experimental class increased after using digital-based flashcard media with a global method. At the time of conducting the pretest, the average score of students was 64.34, while at the time of conducting the posttest, the average score of students increased to 86.88. The score of the control class students during the pretest was 75.81 and when the posttest was carried out, the student's score was 81.97. The results of the hypothesis test were obtained that the value of Sig. two Side p was 0.001 0.05, if the significance value (two Sided p) 0.05, then Ho was rejected and Ha was accepted. So the conclusion is that there is a significant influence on the use of digital-based flashcard media with a global method for the initial reading ability of students in grade I of SD Negeri 116 Pekanbaru.